Properties Of Concrete Containing Rice Husk Ash Under Aggressive Environments Subjected To Wetting And Drying - Putrajaya, Ramadhan Syah (2012)
Rice husk which is agro waste from a rice mill was burned at 700 oe for 6 hours in a gas furnace. The rice husk ash (RHA) was grounded using a laboratory ball mill with porcelain balls. The optimum RHA grinding time was determined. Eight different fineness grades of RHA were examined and it was found that the specific gravity and the fineness of the rice husk ash increase with an increase in grinding time. Even though. the morphology of the RHA changed with grinding. There appears to be an optimum grinding time of approximately 90 min (to 9.52 urn particle size), during which time the compressive strength and strength activity index increases significantly. The use of rice husk ash grounded for 90 min produced concrete with good strength and low porosity. On the other hand, the effect of ground RHA blended cement subjected to 5% sodium chloride solution (NaCI), 5% sodium sulfate solution (Na,S04), and seawater through cyclic wetting and drying was also investigated. Four RHA replacement levels were considered in the study: 10%, 20%, 30%, and 40% by weight of cement. The durability performance of the RHA blended cement exposed to aggressive environment was evaluated through compressive strength, Rapid Chloride Penetrability Test CRCPT), and Rapid Migration Test CRMT). In addition, microstructural changes that occur in specimens due to aggressive environmental effects were identified through thermal analysis, XRD techniques, and SEM. Test results showed that RHA can be satisfactorily used as a cement replacement material in order to increases the durability of concrete.